EPİLEPTİK NÖBETLERİN VE PSÖDONÖBETLERİN AYIRIMINDA OTONOM SİNİR SİSTEMİ TESTLERİ - ARIKANOĞLU, ADALET (Fırat Üniveristesi, 2008)
Epileptik hastalarda iktal ve postiktal dönemde otonom sinir sisteminde (OSS)disfonksiyon gelisebilmektedir. Psikiyatrik hastalıklara baglı psödonöbetleri olanhastalarda ise otonomik fonksiyonların durumu bilinmemektedir. Bu çalısmada birgrup epileptik ve psödonöbetli hastada interiktal ve postiktal dönemde OSSfonksiyonlarını inceleyerek otonom disfonksiyon olusup olusmadıgını ve bununepilepsi ve psödonöbet ayırıcı tanısında kullanılabilirligini arastırdık.Bu çalısmaya Fırat Üniversitesi Hastanesi Nöroloji ve Psikiyatri kliniklerindetakip edilen epilepsili 30 hasta, psödonöbetleri olan 25 hasta ve 20 kisilik saglıklıkontrol grubu alındı. Epilepsi ve psödonöbet gruplarında postiktal ve interiktaldönemde Sempatik deri yanıtı (SDY), RR interval variation (RRIV) ölçümü yapıldı.Epilepsili ve psödonöbetli hastaların postiktal ve interiktal dönem SDY veRRIV ölçümleri arasında istatistiksel olarak anlamlı bir fark yoktu (p>0.05). Epilepsiinteriktalgrubu üst ekstremite SDY latansı, kontrol grubu ile karsılastırıldıgında uzunbulundu (p<0,01). Epilepsi-postiktal grubu üst ekstremite SDY latansı, kontrol grubuile karsılastırıldıgında daha uzamıs olarak bulundu (p<0,001). Epilepsi-interiktal vepostiktal grubu derin solunum RRIV düzeyleri, kontrol grubu ile karsılastırıldıgındaanlamlı düzeyde düsük bulundu (p<0,001). Epilepsi-postiktal ve interiktal grubunormal solunum RRIV, alt ekstremite SDY latansı kontrol grubu ilekarsılastırıldıgında anlamlı fark bulunmadı (p>0.05).Psödonöbet-postiktal grubu derin solunum RRIV düzeyleri, kontrol grubudegerlerinden anlamlı olarak düsük bulundu.(p<0.05). Psödonöbet-interiktal derinsolunum RRIV düzeyleri, psödonöbet-postiktal, interiktal ve kontrol grupları arasındanormal solunum RRIV, üst ve alt ekstremite SDY latansı açısından fark bulunmadı(p>0.05).Bu çalısmada epilepsili hastalarda interiktal dönemde sempatik veparasempatik sistemde disfonksiyon oldugu ve bunun postiktal dönemde dahabelirginlestigi, psödonöbetli hastalarda ise postiktal dönemde parasempatikdisfonksiyon olustugu tesbit edildi.Anahtar kelimeler: Otonom sinir sistemi, Sempatik deri yanıtı, RR ntervalvariation, Epilepsi, Psödonöbet.

In the epileptic patients, autonomic nervous system (ANS) dysfunction can beseen during ictal and postictal period. The autonomic functions state of the patients,who have pseudoseizures due to psychiatric disorders, has not been know. In thisstudy, ANS functions in the epileptic patients and in the patients with pseudoseizuresduring interictal and postictal period has been assessed and autonomic dysfunction asan independent factor in differentiation of epileptic seizures with pseudoseizures hasbeen investigated.In this study, three groups ar formed amongst the patients who seek medicalcare from Firat Univercity Neurology and Psychiatry Clinics and these groups areconsisting of 30 epileptic patients, 25 patients with pseudoseizures and 20 healtyvolunteers. Epileptic and pseudoseizure groups, in postictal and interictal periods,sympathetic skin respond (SSR) and R-R interval variation (RRIV) measurement wasdone.There was no statistically significant difference (p>0.05) between SSR andRRIV measurements of the comparison of postictal and interictal periods of epilepticand pseudoseizure patients. But, latency in epileptic-interictal group was found high(p<0,01) when upper extremity SSR latency was compared with that of control group.Latency in epileptic-postictal group was found more lenghten (p<0,001) when upperextremity SSR latency was compared with that of control group. Deep respirationRRIV levels of epileptic-interictal and postictal group was found notably low whencompared with that of control group (p<0,001). However, there was not anysignificant difference when normal respiration RRIV, lower extremity SSR latency ofepileptic postical and interictal group was compared with the control group (p>0.05).RRIV levels of deep respiration of pseudoseizure-postictal group was foundnotably low when compared with that of control group (p<0.05). There was not anysignificant difference in deep and normal respiration RRIV levels, upper and lowerextremity SSR latency of pseudo-seizure-interictal and postictal group, whencompared with that of control group (p>0.05).In this study, it has been observed that in the epileptic patient groupsympathetic and parasympathetic systems dysfunction has been seen during interictalperiod and it is more significant during postical period where as only parasympatheticsystem disfunction has been seen during postictal system in the pseudo-seizurepatients group.Key Words : Autonomic nervous system, sympathetic skin respons, RRInterval variation, Epilepsy, Pseudo-seizure.
Autonomic nervous system tests in differentiation of epileptic seizures with pseudoseizures
Keywords: Nöroloji